PENGARUH PENGUASAAN GETARAN TERHADAP HASIL BELAJAR IPA TERPADU SISWA PADA MATERI POKOK BUNYI SMP NEGERI 5 SIPIROK - Siregar, Dedes Asriani (Jurnal Physics Education (PhysEdu), 2023)
The aims to ascertain whether not any significant effect between the getraran governance basic towar physic outcomes topic bunyi. physic learning outcomes topic bunyi is a factor supporting the success of student in learning, in fact the result of learning gained go while KKM “65”. This condition should not be allowed because resulted in the national education goals are not, achieved. Overcomes this problem needs to control the getaran governance basic teacher be better. The eksperiment was conducted at SMP Negeri 5 Sipirok. 59 people as population and sampel werw taken with total sampling, are 59 people. The method used descriptif method and data collectioned test, multiplechoise. The data obtain, were processed two stages,namely deskriftif analysis to see a correlation “r” product moment and to see wheter there is a significant effect between the two variables used ttest. the result of the data obtained an average variable x=70,35 and variable y=68,77, tcount=7,54 and ttable=2,085 then t count greather than t table (7,54>2,085), so this hipotesis can achieved.